Interactions of Large‐Scale Dynamics and Madden‐Julian Oscillation Propagation in Multi‐Model Simulations. Issue 11 (27th May 2021) - Heath, Ashley; Gonzalez, Alex O.; Gehne, Maria; Jaramillo, Alejandro
Abstract: The underrepresentation of the Madden‐Julian Oscillation (MJO) in climate models remains a challenge, limiting our ability to improve medium‐ to extended‐range atmospheric prediction. Motivated by recent work identifying the importance of the ratio of equatorial Rossby (ER) to Kelvin wave circulations in MJO propagation, this study examines MJO dynamics in 25 climate model simulations. We find that poor MJO models simulate anomalously large ER wave circulations to the west and small Kelvin and ER wave circulations to the east of the convective center. To quantify the role of circulation asymmetries in MJO propagation, we formulate a new west/east (W/E) zonal wind speed ratio. Our W/E ratio differs from other similar metrics in that it implicitly accounts for the ER wave gyres and it can be applied at all levels. Poor model ER wave biases are associated with excessive 700–1000‐hPa convergence, convection, and vertical moisture advection co‐located and west of the convective center while Kelvin and ER wave biases to the east are associated with a weaker dry anomaly and smaller horizontal moisture advection at 450–750‐hPa. Together, these biases help explain the stationary and slight westward MJO propagation in poor models. Space‐time spectral analyses of the zonal wind and precipitation confirm that good models produce realistic power, coherence, and phase for the MJO while poor models vastly underrepresent Kelvin waves and the MJO. Even though Kelvin waves are more realistic in good models, there are still model‐wide biases in circulation‐convection coupling for ER waves and Kelvin waves. Plain Language Summary: Intraseasonal variability lies between weather and climate time scales and has been shown to extend the traditional two‐week weather predictability limit to up to five weeks. The Madden‐Julian Oscillation (MJO) is an intraseasonal atmospheric mode that couples tropical atmospheric clouds and circulations. Key features of the MJO include a large region of strong clouds and precipitation surrounded by large regions of dry conditions that together propagate eastward from the Indian Ocean to the Pacific Ocean. The MJO contains eastward winds to the west and westward winds to the east of the strong clouds near the surface and reversed winds in the upper atmosphere. This study investigates the differences of the large‐scale circulations associated with the MJO between a set of six good and poor models to explain the fidelity of MJO propagation. We find that poor models tend to have too strong of circulations and clouds in the lower atmosphere co‐located with and to the west of the MJO's cloud center, causing stagnant, or even westward, propagation. A space and time investigation into other atmospheric modes of variability demonstrates that all models, especially poor models, have significant biases in the interactions between large‐scale circulations and clouds. Key Points: A west/east zonal wind speed ratio shows models with a large Rossby wave or small Kelvin wave response to convection have a stagnant Madden‐Julian Oscillation (MJO) Poor model Rossby and Kelvin waves are associated with anomalous moistening co‐located with convection and drying to the east, respectively Spectral analyses show deficient MJO, Rossby, and Kelvin wave zonal wind and rainfall in poor models but suggest model‐wide coupling biases